Assessing Utilization and Environmental Risks of Important Genes in Plant Abiotic Stress Tolerance - Khan, Mohammad S.; Khan, Muhammad A.; Ahmad, Dawood (Frontiers in Plant Science, 2016)
Transgenic plants with improved salt and drought stress tolerance have been developed with a large number of abiotic stress-related genes. Among these, the most extensively used genes are the glycine betaine biosynthetic codA, the DREB transcription factors, and vacuolar membrane Na+/H+ antiporters. The use of codA, DREBs, and Na+/H+ antiporters in transgenic plants has conferred stress tolerance and improved plant phenotype. However, the future deployment and commercialization of these plants depend on their safety to the environment. Addressing environmental risk assessment is challenging since mechanisms governing abiotic stress tolerance are much more complex than that of insect resistance and herbicide tolerance traits, which have been considered to date. Therefore, questions arise, whether abiotic stress tolerance genes need additional considerations and new measurements in risk assessment and, whether these genes would have effects on weediness and invasiveness potential of transgenic plants? While considering these concerns, the environmental risk assessment of abiotic stress tolerance genes would need to focus on the magnitude of stress tolerance, plant phenotype and characteristics of the potential receiving environment.These genes need careful evaluation based on their encoded proteins, underlying mechanisms, level of stress tolerance, phenotype of transgenic plant and the potential receiving environment. In the present review, we discuss environmental concerns and likelihood of concerns associated with the use of abiotic stress tolerance genes. Based on our analysis, we conclude that the uses of these genes in domesticated crop plants are safe for the environment. Risk assessment, however, should be carefully conducted on biofeedstocks and perennial plants taking into account plant phenotype and the potential receiving environment.